GEOLINGUISTIK: VARIASI DIALEK DAN LEMAHNYA PEMERTAHANAN BAHASA SUNDA OLEH GENERASI MUDA - sulastri1, ai (JURNAL GEOGRAFI, 2024)
Indonesia has a variety of regional languages, and the geographical location of each region will also determine language variations. The forms of language variation can be distinguishedfrom geographical, social, and temporal locations. Sundanese is one of the various languagesowned by Indonesia with a variety of dialect variations and ranks second with the largest number of speakers in Indonesia. The current development of Science and Technology (Science and Technology) greatly influences dynamic life, especially in aspects of acculturation of language or linguistics. This will cause the fading of Sundanese as a regional language, and variations of the original Sundanese dialect will begin to erode due to the environment of the younger generation. The purpose of this writing is to find out the various variations of Sundanese dialects and overcome the threat of language extinction due to the weak maintenance of Sundanese by the younger generation which is studied from a geographical perspective. The research method used is a systematic literature review (SLR), namely a literature search and Geolinguistic theoretical methods. One of the results of this study is thatfrom a geographical point of view efforts to maintain the Sundanese language need to increaseaccessibility through infrastructure development so that the mobility of people from various regions can help strengthen relations between regions which in turn can maintain Sundanese and local regional dialects. It is hoped that the results of this research can provide appropriateefforts to maintain the Sundanese language and dialect.